Sustaining Social Security in an Era of Population Aging - Turner, John A. (W.E. Upjohn Institute, 2023)
John A. Turner offers a set of reforms for restoring solvency to Social Security that are deemed to have merit in the current political climate. These reforms relate to several vexing issues including increased life expectancy, the growing relationship between income and life expectancy, the declines in the physical demands of jobs, growing income inequality, and the pattern of poverty increasing at older ages.